What shapes the governance of the dairy value chain in Vietnam? Insights from Ba‐Vì milkshed (Hanoi). Issue 2 (1st March 2017) - Nguyen, Mai‐Huong; Duteurtre, Guillaume; Moustier, Paule
Abstract : Vietnam has experienced a rapid growth in the dairy sector since the early 2000s. However, the organization of the sector is said to be inequitable and its motivational mechanisms are not sufficient to ensure the development of smallholder farmers. To assess smallholders' prospects in the upgrading process of the whole dairy sector, we conducted a study in Ba‐Vì district, the largest "milkshed" in the Red River Delta, which has undergone a remarkable transition from state‐owned concentrated production to smallholder farms. The study focuses on value chain governance and upgrading strategies. The local dairy value chain is dominated by smallholders and characterized by contractual relations between private milk collectors and industrial, semi‐industrial, and cottage processors. The local chain is featured by a mixed relational‐captive governance pattern. Relational governance characterizes the two sub‐channels in which small‐scale industries operate. Captive governance describes the leading role of a medium‐size dairy firm that has invested in UHT processing facilities and benefited from support from the local government. The strong role of public authorities and some challenges for chain upgrading are discussed.